Wyznaczniki językowo-stylistyczne obrazu Wielkopolski w Listach z narodowej pielgrzymki Ryszarda Berwińskiego - Maćkowiak, Krzysztof (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article analyzes Listy z narodowej pielgrzymki ( Letters from the national pilgrimage ) by Ryszard Berwiński. It is a series of five texts written in prose in which the author tells his impressions from a trip to the vicinity of Gopło, probably in the summer of 1838. At that time, such escapades became fashionable in Poland. The aim of the study is to define the lexis used in the Letters to describe the cultural landscape of Greater Poland in order to identify the aforementioned word material and analyse the way it is used.